Trade, Informal Employment and Labor Adjustment Costs - Arias, Javier; Artuc, Erhan; Lederman, Daniel; Rojas, Diego (World Bank, Washington, DC, 2014)
Informal employment is ubiquitous in developing countries, but few studies have estimated workers' switching costs between informal and formal employment. This paper builds on the empirical literature grounded in discrete choice models to estimate these costs. The results suggest that inter-industry labor mobility costs are large, but entry costs into informal employment are significantly lower than the costs of entry in formal employment. Simulations of labor-market adjustments caused by a trade-related fall in manufacturing goods prices indicate that the share of informally employed workers rises after liberalization, but this is due to entry into the labor market by previously idle labor.